Assessing the efficiency level of the “poverty alleviation through agriculture project”: A case study of fixed observation points in China - Yan, Shuya; Li, Lipeng; Sarkar, Apurbo; Yang, Guotao (Frontiers in Sustainable Food Systems, 2022)
In the modern era, development organizations and governments worldwide are undertaking various policies and projects to eradicate poverty. However, there is a lack of evidence that can trigger the efficiency level of those. Based on the survey data of the Ministry of Agriculture and Rural Affairs, which was acquired at rural fixed observation points across 31 provinces of China from 2012 to 2016, the study evaluates the overall efficiency, stage-specific efficiency, and indicator-based efficiency of “Poverty alleviation through agriculture projects of China”. First of all, the entire process of agricultural poverty relief is divided into two stages: (i) agricultural production and (ii) social governance. Accordingly, the study proposes a two-stage theoretical analysis framework for agricultural poverty relief and decomposes the mechanisms; it also discusses the potential for improved efficiency levels in both agricultural production efficiency and social governance efficiency. Therefore, we utilize the two-stage dynamic data envelopment analysis (DEA) model to outline the findings. The outcomes showed the efficiency level of the projects can play an important role in addressing rural poverty in China. This study’s major findings are summarized as follows: (i) the overall efficiency of the projects tends to be stable undauntedly. While agricultural production efficiency is the major cause and social governance efficiency in the second stage has been a minor cause for maintaining a relatively lower level of overall efficiency. (ii) There is significant room for improving the efficiency of certain input indicators (including total labor force, productive fixed assets, and education attainment of rural labor) and intermediate variables (i.e., income gap of village households). However, a limited room has been found for certain output indicators (including the total output of grain, the poverty elimination index, and an aggregate index of social harmony). Thus, in China, poverty alleviation projects should be revitalized and targeted instead of concentrated. It is required to advance a long-term structure for rural poverty and promote the smooth transition of the poverty alleviation projects and working criteria. Moreover, the government should strengthen the top-level design for addressing the relative poverty problem and incorporate it into the rural revitalization strategy.